Immunogenicity Following Administration of BNT162b2 and Ad26.COV2.S COVID-19 Vaccines in the Pregnant Population during the Third Trimester - Ioana Mihaela Citu; Cosmin Citu; Florin Gorun; Ioan Sas; Larisa Tomescu; Radu Neamtu; Andrei Motoc; Oana Maria Gorun; Bogdan Burlea; Felix Bratosin; Daniel Malita (Viruses, 2022)
Globally, COVID-19 vaccines are currently being used to prevent transmission and to reduce morbidity and death associated with SARS-CoV-2 infection. Current research reveals that vaccines such as BNT162b2 and Ad26.COV2.S are highly immunogenic and have high short-term effectiveness for most of the known viral variants. Clinical trials showed satisfying results in the general population, but the reluctance in testing and vaccinating pregnant women left this category with little evidence regarding the safety, efficacy, and immunogenicity following COVID-19 vaccination. With the worldwide incidence of COVID-19 remaining high and the possibility of new transmissible SARS-CoV-2 mutations, data on vaccination effectiveness and antibody dynamics in pregnant patients are critical for determining the need for special care or further booster doses. An observational study was developed to evaluate pregnant women receiving the complete COVID-19 vaccination scheme using the BNT162b2 and Ad26.COV2.S, and determine pregnancy-related outcomes in the mothers and their newborns, as well as determining adverse events after vaccination and immunogenicity of vaccines during four months. There were no abnormal findings in pregnancy and newborn characteristics comparing vaccinated versus unvaccinated pregnant women. COVID-19 seropositive pregnant women had significantly higher spike antibody titers than seronegative patients with similar characteristics, although they were more likely to develop fever and lymphadenopathy following vaccination. The same group of pregnant women showed no statistically significant differences in antibody titers during a 4-month period when compared with case-matched non-pregnant women. The BNT162b2 and Ad26.COV2.S vaccines are safe to administer during the third trimester of pregnancy, while their safety, efficacy, and immunogenicity remain similar to those of the general population.